2011
DOI: 10.1002/lary.21425
|View full text |Cite
|
Sign up to set email alerts
|

Variable changes in PET activity before and after rTMS treatment for tinnitus

Abstract: Objective/Hypothesis Determine whether low-frequency rTMS improves tinnitus by decreasing neural activity in auditory processing regions of the temporal cortex and the utility of PET for targeting treatment. Study Design Randomized, sham-controlled crossover. Methods Patients received a 5-day course of active and sham 1-Hz rTMS (1800 pulses at 110% of motor threshold) to the temporal cortex, with a week separating active and sham treatment. Visual analogue ratings of tinnitus loudness (VARL) were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Thus, in some cases, the coverage of rTMS may include the auditory cortex. Even where there are no direct interactions, propagation of brain activity from the stimulant foci can result in widespread changes [Mennemeier et al, 2011]. It seemed that targeting on the auditory cortex was not more mainstreamed into the tinnitus treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, in some cases, the coverage of rTMS may include the auditory cortex. Even where there are no direct interactions, propagation of brain activity from the stimulant foci can result in widespread changes [Mennemeier et al, 2011]. It seemed that targeting on the auditory cortex was not more mainstreamed into the tinnitus treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This can be accomplished using a combination of positron emission tomography and computed tomography (PET-CT), which indicates the areas that experience the highest levels of cortical activation [Mennemeier et al, 2011]. However, this is an invasive procedure and requires that researchers first convince patients to submit to injection of radioactive isotopes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Progress in functional imaging has helped explain the pathophysiology and identified brain lesions related to tinnitus [32]. Several studies have reported that positron emission tomography (PET) can be used to identify the region of unbalanced cortical activity where rTMS could be applied [33,34]; however, controversy remains regarding the usefulness of PET for rTMS targeting [35] and the function of PET and other neuroimaging modalities in determining the stimulation site is debatable. Rossi [36] reported that stimulation (5 days, 1-Hz rTMS) in the left temporoparietal area was effec- tive and not related to tinnitus laterality.…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%